Sifat fisiko-kimia yoghurt kacang hijau (Vigna radiata) dengan variasi jenis starter bakteri dan pemanis sari kurma sukkari (Phoenix dactilyfera L) sebagai pemanis alami dan sumber antioksidan - Ika Dyah Kumalasari; Indri Fajriyati (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Yogurt based on mung bean juice is good to consume because it is low in fat and lactose. Sukkari dates have the potential to be used as a natural sweetener because they contain simple sugars that are easily digested by the body. In addition, there is an antioxidant content that can fight free radicals. This study aims to determine the physico-chemical properties of mung bean yogurt. Dependent variables include pH value, viscosity, moisture content, ash content, fat content, protein content, carbohydrate content, total sugar content, and antioxidants. Independent variables include the type of bacterial starter (S1: Lactobacillus bulgaricus and Streptococcus thermophilus; S2: Biokul Plain) and sweetener variations (K1; K2; K3). The study used a Complete Randomized Design (RAL) with a statistical test of Two Ways ANOVA and a post hoc test of Tukey. The results showed that the type of bacterial starter and the variety of sweeteners had a significant effect on the physico-chemical properties of yogurt. The highest pH and viscosity values in the S2K3 sample were 4.67 and 3.18 m. Pas; the highest water content in the S1K1 sample was 86.5 %; the highest ash content and fat content in the S2K3 sample were 0.66 % and 4.82 %; the highest protein content, carbohydrate content (by different), and total sugar content in the S1K3 sample were 2.35 %, 10.11 %, and 9.78 %; and the highest antioxidant in the S2K3 sample with an AAI value of 1.54.